Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{f_n(x)\}_{n\in \Bbb N}$ be a sequence of polynomials defined inductively as $$\begin{matrix} f_1(x) & = & (x-2)^2 & \\ f_{n+1}(x)& = & (f_n(x)-2)^2, &\text{ for all }n\ge 1.\end{matrix}$$

Let $a_n$ and $b_n$ respectively denote the constant term and the coefficient of $x$ in $f_n(x)$. Then

  1. $(\text A)\,\, a_n=4, b_n=-4^n$
  2. $(\text B)\,\,a_n=4, b_n=-4n^2$
  3. $(\text C)\,\, a_n=4^{(n-1)!}, b_n=-4^n$
  4. $(\text C)\,\, a_n=4^{(n-1)!}, b_n=-4n^2$

Please help me how to solve this problem. I am not able to solve it.

The problem can be found on this link.

share|cite|improve this question
the link of the question is – amitabha Aug 4 '13 at 14:33



$f_2(x)=(f_1(x)-2)^2$ $=(x^2-4x+4-2)^2=(2-4x+x^2)^2=2^2+2\cdot2(-4x)+\cdots=4-4^2x+\cdots$

$f_3(x)=(f_2(x)-2)^2$ $=(4-2^4x+\cdots-2)^2=(2-2^4x+\cdots)^2=2^2-2\cdot2\cdot4^2x+\cdots=2^2-4^3x+\cdots$

$f_4(x)=(f_3(x)-2)^2$ $=(2^2-4^3x+\cdots-2)^2=(2-4^3x+\cdots)^2=2^2-2\cdot2\cdot2^6x+\cdots=2^2-4^4x+\cdots$

$f_5(x)=(f_4(x)-2)^2$ $=(4-4^4x+\cdots)^2=(2-4^4x+\cdots)^2=2^2-2\cdot2\cdot2^8x+\cdots=2^2-4^5x+\cdots$

So, $a_n=4$

$b_n=-4^{(n \text{ th term of } 1,2,3,4,5)}=-4^n$

share|cite|improve this answer

The following is a proof by induction of the statement $(\forall n\in \Bbb N)(a_n=4\land b_n=-4^n)$.

First start by noting that $\text{deg}(f_n(x))=2^n$, for all $n\in \Bbb N$. Therefore, for certain $c_{2^n}, c_{2^n-1}, \ldots , c_2, c_1 \color{gray}{=b_n}, c_0\color{gray}{=a_n}\in \Bbb Z$ it holds that $$f_n(x)=c_{2^n}x^{2^n}+\cdots + c_2x^2+b_nx+a_n.$$

$\bbox[5px,border:2px solid #0000FF]{(\forall n\in \Bbb N)(a_n=4)}$

$\bullet$ Clearly $a_1=4$.
$\bullet$ Let $n\in \Bbb N$ such that $a_n=4$.
$\,\,\,$ Since $f_{n+1}(x)=(f_n(x)-2)^2=(c_{2^n}x^{(2^n)}+\cdots +b_nx+(a_n-2))^2$, it clearly follows that the
$\,\,\,$ constant term in $f_{n+1}(x)$ is $\color{gray}{(a_n-2)^2=(4-2)^2=}4$.

$\therefore (\forall n\in \Bbb N)(a_n=4)$

$\bbox[5px,border:2px solid #0000FF]{(\forall n\in \Bbb N)(b_n=-4^n)}$

$\bullet$ Clearly $b_1=-4^1$.
$\bullet$ Let $n\in \Bbb N$ and suppose $b_n=-4^n$. Since $$\begin{align}f_{n+1}(x)=(f_n(x)-2)^2&=(c_{2^n}x^{(2^n)}+\cdots +b_nx+(4-2))^2 \\ &=(c_{2^n}x^{(2^n)}+\cdots +b_nx+2))(c_{2^n}x^{(2^n)}+\cdots +b_nx+2),\end{align}$$

it easy to to see that the coefficient of $x$ in $f_{n+1}(x)$ is $\color{gray}{2b_n+2b_n=4b_n=4\cdot (-4^n)=}-4^{n+1}$.

$\therefore (\forall n\in \Bbb N)(b_n=-4^n)$.

The parts regarding the coefficients $a_{n+1}$ and $b_{n+1}$ can be rigorously proved by induction or by applying the multinomial theorem.

share|cite|improve this answer

Induction on $\;n\;$ :


$$f_{n+1}(0)=\left(f_n(0)-2\right)^2\stackrel{\text{Ind. Hyp.}}=(4-2)^2=4$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.